The Political Role of Corporate Citizens - Svedberg Helgesson, Karin. author. aut Link
XV, 229 p.
Keywords: This volume provides an interdisciplinary analysis on the political role of corporations in society by using the analytical device of corporate citizenship. It questions what ideas on corporate citizenship may say about the ongoing publicization of the corporation and the implications of these developments for the public domain and welfare state.